2005
DOI: 10.1093/clipsy.bpi030
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Prevention in Older Adults.

Abstract: Older adults have high rates of suicide in the United States and worldwide; rates vary markedly by gender, race, and ethnicity. Ceropsychology practice guidelines (e.g., American Psychological Association [APA], 2004) indicate the need for assessment and treatment practices specific to older adults, as the phenomenology of mental disorders and psychotherapeutic change processes may shift across the lifespan. Inadequacies in the available knowledge base and in the education and training of clinicians have slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 140 publications
(179 reference statements)
0
20
0
Order By: Relevance
“…In a study of suicide deaths in older adults, Waern et al [1999] found that 38% expressed thoughts of suicide to a clinician, but 8% denied having suicidal thoughts even when asked directly. Although past history of suicidal behavior is an important risk marker for suicide [Heisel and Duberstein, 2005], those who have never previously engaged in suicidal behavior nonetheless account for 58% [Rubenowitz et al, 2001] to 75% [Phillips et al, 2003] of deaths by suicide in older age. Although our data suggest that there is a relationship between FO and suicide ideation, the implications of FO for lethal and nonlethal self-harm are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of suicide deaths in older adults, Waern et al [1999] found that 38% expressed thoughts of suicide to a clinician, but 8% denied having suicidal thoughts even when asked directly. Although past history of suicidal behavior is an important risk marker for suicide [Heisel and Duberstein, 2005], those who have never previously engaged in suicidal behavior nonetheless account for 58% [Rubenowitz et al, 2001] to 75% [Phillips et al, 2003] of deaths by suicide in older age. Although our data suggest that there is a relationship between FO and suicide ideation, the implications of FO for lethal and nonlethal self-harm are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative reviews have suggested an association between community-based depression screening (CDS) and reduced suicide risk for older adults (Blow et al 2006;Grek et al 2006;Heisel and Duberstein 2005;Dombrovski and Szanto 2005;Mann et al 2005). To our knowledge, there are no large intervention studies using CDS for elderly suicide prevention, nor systematic reviews that provide a quantitative synthesis of studies regarding the effectiveness of CDS on the suicide risk.…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, and race are consistent risk indices: older white men are overrepresented among suicides (15,16). Late-life suicide rates have declined steadily since the 1930s, except for a temporary increase in the 1980s (7).…”
Section: Epidemiology Of Suicide Among Older Adults In Canadamentioning
confidence: 99%
“…Late-life suicide risk is associated with suicidal ideation and behaviour, mental illness, personality vulnerability, medical illness and physical impairment, losses and poor social supports, and functional limitation (15,16). Resiliency factors include integration in social networks and clubs, religious practice, having a hobby, and perceiving that life is meaningful and worth living.…”
Section: Conclusion and Suggested Future Stepsmentioning
confidence: 99%